Admission systolic blood pressure as a prognostic predictor of acute decompensated heart failure: A report from the KCHF registry - Kawase, Yuichi (PLoS One, 2021)
BACKGROUND: Admission systolic blood pressure has emerged as a predictor of postdischarge outcomes of patients with acute decompensated heart failure; however, its validity in varied clinical conditions of this patient subset is unclear. The aim of this study was to further explore the prognostic value of admission systolic blood pressure in patients with acute decompensated heart failure. METHODS: The Kyoto Congestive Heart Failure (KCHF) registry is a prospective, observational, multicenter cohort study enrolling consecutive patients with acute decompensated heart failure from 19 participating hospitals in Japan. Clinical characteristics at baseline and prognosis were examined by the following value range of admission systolic blood pressure: <100, 100–139, and ≥140 mmHg. The primary outcome measure was defined as all-cause death after discharge. Subgroup analyses were done for prior hospitalization for heart failure, hypertension, left ventricular ejection fraction, and medications at discharge. We excluded patients with acute coronary syndrome or insufficient data. RESULTS: We analyzed 3564 patients discharged alive out of 3804 patients hospitalized for acute decompensated heart failure. In the entire cohort, lower admission systolic blood pressure was associated with poor outcomes (1-year cumulative incidence of all-cause death: <100 mmHg, 26.8%; 100–139 mmHg, 20.2%; and ≥140 mmHg, 15.1%, p<0.001). The magnitude of the effect of lower admission systolic blood pressure for postdischarge all-cause death was greater in patients with prior hospitalization for heart failure, heart failure with reduced left ventricular ejection fraction, and β-blocker use at discharge than in those without. CONCLUSIONS: Admission systolic blood pressure is useful for postdischarge risk stratification in patients with acute decompensated heart failure. Its magnitude of the effect as a prognostic predictor may differ across clinical conditions of patients.